A new mathematical model for the glycolysis phenomenon involving Caputo fractional derivative: Well posedness, stability and bifurcation. (January 2021) - Belmahi, Naziha; Shawagfeh, Nabil
Abstract: In this work, we propose a new model for the glycolysis phenomenon involving Caputo derivative. We establish rigourously the existence and uniqueness of a positive solution to this system, then we discuss the stability and the Hopf bifurcation. The dynamics exhibited by the fractional system showed that the new model represents the glycolysis phenomenon more accurately than the corresponding classical first order system. Differences are illustrated by performing some numerical simulations, in which our main findings are confirmed.